AI-Driven Applications for Psychological Counseling: Global Trends and Impacts - Tissa Maharani; Hari Setiabudi Husni (International Journal Multidisciplinary Science, 2026)
The integration of Artificial Intelligence (AI) in psychological counseling has accelerated, especially through mobile and web-based platforms. AI-based systems such as chatbots, virtual therapists, and intelligent monitoring tools have transformed how individuals access mental health services. These technologies offer scalable, real-time support, reduce stigma barriers, and augment the work of human counselors. However, critical questions remain regarding their accuracy, ethical risks, cultural relevance, and emotional authenticity. This study applies a Systematic Literature Review (SLR) guided by the PRISMA method to synthesize peer-reviewed research on the forms, functions, and impacts of AI implementation in psychological counseling from 2016 to 2026. The review includes 25 valid references, with 80% drawn from online scientific journals and over half from international sources. Findings show that AI tools are widely used for mental health screening, psychoeducation, and therapy delivery. Positive impacts include accessibility and cost-efficiency, while negative concerns involve data privacy, algorithmic bias, and trustworthiness. Both counselor and user perspectives reveal a complex interplay between digital convenience and human empathy. The study concludes that while AI is a promising support mechanism in mental health services, it must be applied with cultural sensitivity, ethical safeguards, and professional integration. This review provides a foundation for future research and policy development concerning AI’s responsible role in psychological support systems.